Advances in experimental social psychology. - Zanna, Mark P. (Advances in experimental social psychology, 2001)
Advances in Experimental Social Psychology continues to be one of the most sought after and most often cited series in this field. Containing contributions of major empirical and theoretical interest, this series represents the best and the brightest in new research, theory, and practice in social psychology.